2000
DOI: 10.1211/0022357001774075
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Kaempferol as a Monoamine Oxidase Inhibitor and Potential Neuroprotectant in Extracts of Ginkgo Biloba Leaves

Abstract: The effects of Ginkgo biloba leaf extract on rat brain or livermonoamine oxidase (MAO)-A and -B activity, biogenic amine concentration in nervous tissue, N-methyl-D-aspartate (NMDA)- and N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine (DSP-4)-induced neurotoxicity and antioxidant activity was investigated to determine the effects of the extract on monoamine catabolism and neuroprotection. Ginkgo biloba leaf extract was shown to produce in-vitro inhibition of rat brain MAO-A and -B. The Ginkgo biloba extract was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(71 citation statements)
references
References 28 publications
2
69
0
Order By: Relevance
“…Because benzoflavanones have not previously been reported to act on MAOA as inhibitors, [28][29][30] and the inhibitory effect of one of benzoflavones, 3-(4-methoxyphenyl)-2,3-dihydro-1H-benzo[ f ] chromen-1-one used in this study is comparable to that of clorgyline which is known as MAOA inhibitor, 31 our findings are meaningful.…”
supporting
confidence: 51%
“…Because benzoflavanones have not previously been reported to act on MAOA as inhibitors, [28][29][30] and the inhibitory effect of one of benzoflavones, 3-(4-methoxyphenyl)-2,3-dihydro-1H-benzo[ f ] chromen-1-one used in this study is comparable to that of clorgyline which is known as MAOA inhibitor, 31 our findings are meaningful.…”
supporting
confidence: 51%
“…, and demonstrated anti-depressant actions in mice 40 . It is not clear how Maca acts on reducing psychological symptoms, although flavonoids present in Maca may be responsible for these actions [40][41][42][43] . Interestingly, the reduced psychological symptoms (depression and anxiety) did not correlate with reduced vasomotor symptoms (hot flushes), despite a strong association between the two 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…39) It also has been shown that the MAO-B activity is elevated with age, which is directly related to PD, and MAO-B inhibitor has been used as a classic drug for clinical treatment. In the PD mouse model, MPTP was metabolized selectively by MAO-B to the active toxin MPP Ï© .…”
Section: Discussionmentioning
confidence: 99%